Coffee Shop as a Space for Learning English Speaking Skills for Underprivileged Students - Authar, Nailul; Saputri, Tiyas; Djuwari, Djuwari; Fitriyah, Fifi Khoirul (Indonesia Berdaya, 2022)
Take a look at from the current situation, drinking a cup of coffee in a coffee shop becomes a living style trend in society. Not only teenagers experience enjoyable and comfort there, but also adult people feel the same too. This phenomenon are happening right now. Seeing this situation, it would be better if the activity of drinking coffee that was liked by the general public could be a way to overcome boredom in learning English, especially in speaking skills. However, not all students can get these facilities due to economic factors. They are called "Underprivileged Students". So, with this activity, it is hoped that it can help disadvantaged students so that they can get additional English education. The ranking shows that the English ability of the people in Indonesia is in the very low category. Without exception, teenagers or students in Surabaya. Especially those who experience this problem are underprivileged students, because they only get education through formal schools which are only carried out in class or online so they are less effective. As stated in the sub-chapter description of partner problems, there are solutions to overcome problems with partners. One of the creative ideas that can be done is to learn English at the Coffee Shop. This activity will take place through 4 stages, the first is pre-activity, the second is the general stage which includes the inauguration of the activity, the third is the core of the activity, and the fourth is the evaluation of the activity.